1993
DOI: 10.1007/bf02891700
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase and changes of microbial community in soil

Abstract: Enrichment of soil with chitin (0.6%) significantly stimulated growth of chitinolytic microorganisms (the relative proportion was increased from 1.7 to 26.5%) and the formation of chitinase in soil. In a soil enriched with chitin and glucose (0.6%), the proportion of chitinolytic microorganisms remained similar to that in the nonenriched soil (1.4%), the enzyme formation was negatively affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…A decrease in chitinase activity such as we observed indicates a reduction in bacterial abundance, a reduction in the importance of chitin as a source of C and N, or an increase in the availability of more labile forms of organic matter (Hanzlikova and Jandera 1993). As chitin is intermediate in its resistance to microbial metabolism, its synthesis is only induced when other, more labile C and N sources are absent (Hanzlikova and Jandera 1993). In general, this trend is consistent with our results, as chitinase activity and C:N ratios were reduced relative to the Control in year 3 (Miesel 2009).…”
Section: Soil Enzyme Activitymentioning
confidence: 63%
See 2 more Smart Citations
“…A decrease in chitinase activity such as we observed indicates a reduction in bacterial abundance, a reduction in the importance of chitin as a source of C and N, or an increase in the availability of more labile forms of organic matter (Hanzlikova and Jandera 1993). As chitin is intermediate in its resistance to microbial metabolism, its synthesis is only induced when other, more labile C and N sources are absent (Hanzlikova and Jandera 1993). In general, this trend is consistent with our results, as chitinase activity and C:N ratios were reduced relative to the Control in year 3 (Miesel 2009).…”
Section: Soil Enzyme Activitymentioning
confidence: 63%
“…Boyle et al (2005) showed that phosphatase activity increased in a composite treatment (thinning, burning and litter reduction) and was not affected by thinning alone, relative to a control; however, this effect was observed only during wet rather than dry soil conditions. A decrease in chitinase activity such as we observed indicates a reduction in bacterial abundance, a reduction in the importance of chitin as a source of C and N, or an increase in the availability of more labile forms of organic matter (Hanzlikova and Jandera 1993). As chitin is intermediate in its resistance to microbial metabolism, its synthesis is only induced when other, more labile C and N sources are absent (Hanzlikova and Jandera 1993).…”
Section: Soil Enzyme Activitymentioning
confidence: 79%
See 1 more Smart Citation
“…Fire can preferentially favor chitonolytic organisms (mainly bacteria) to produce more chitin in the post-fire environment [81]. In high N environment, as in the PF stand, chitin can depress chitinase (NAG) activity [82].…”
Section: Aboveground-belowground Controls On Nutrient Bioavailabilitymentioning
confidence: 99%
“…Acid phosphatase was chosen as an indicator of overall microbial activity because its activity is strongly correlated with microbial biomass (Kandeler and Edler 1993), microbial biomass N (Clarholm 1993), fungal hyphal length (Häussling and Marschner 1989), and N mineralization (Decker et al 1999). Chitinase is a bacterial enzyme that catalyzes the breakdown of chitin, a byproduct of both fungi and arthropods, into carbohydrates and inorganic N. As chitin is intermediate in its resistance to microbial metabolism, the synthesis of chitinase is only induced when other, more labile C and N sources are absent (Hanzlikova and Jandera 1993). Phenol oxidase is produced primarily by white rot fungi and is specific for highly recalcitrant organic matter, such as lignin (Carlile and Watkinson 1994).…”
Section: Soil Sampling and Laboratory Analysismentioning
confidence: 99%